Malim Belief System in The Toba Batak Community in Air Kulim Village, Bathin Solapan District, Bengkalis Regency - Rizky Metro Siallagan; Suharti; Mutia Kahanna (Kirana Publisher (KNPub), 2024)
This research is entitled